Electrode Structuring via Carbon Nanotubes and Nafion Ionomer-Coated TiO2 Enhances the Durability of Proton Exchange Membrane Fuel Cells Under Carbon Corrosion Conditions - Kim, Ohsub; Lim, Katie Heeyum; Kwon, Junhwa; Yoo, Sung Jong; Kim, Jin Young; Cho, Sung Ki; Park, Hyun S.; Lee, So Young; Seo, Bora; Kim, Myeong-Geun; Jang, Jong Hyun; Park, Hee-Young (Wiley - V C H Verlag GmbbH & Co., 2025)
The widespread implementation of proton exchange membrane fuel cells (PEMFCs) is being delayed by their inadequate durability, particularly that of the cathode. To address this problem, two corrosion-resistant additives are introduced to mitigate the structural collapse of the PEMFC cathode due to carbon corrosion: carbon nanotubes (CNTs) and a composite consisting of TiO2 coated with the Nafion ionomer (NT composite). CNTs give rise to a micrometer-scale porous structure and improve the durability of the electrodes by preserving their structure during PEMFC operation. In tandem with the CNTs, the NT composite reinforces the structure with sub-micrometer-scale pores and maintains a stable ionomer distribution to promote gas transport and proton transfer within the electrode, respectively. The textured and reinforced structure is maintained even after carbon corrosion, thus significantly increasing the durability of PEMFCs, with a performance degradation of only 0.3% (i.e., the durability is approximate to 37 times higher) after accelerated durability tests. Moreover, the initial performance is comparable to that of state-of-the-art electrodes with the conventional Pt/C catalyst. The significant enhancement of the durability of PEMFCs by creating an advanced electrode structure with suitable additives is expected to facilitate their development for various applications and practical commercialization.